If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -5 = (-8) Reorder the terms: -5 + y = (-8) -5 + y = -8 Solving -5 + y = -8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + y = -8 + 5 Combine like terms: -5 + 5 = 0 0 + y = -8 + 5 y = -8 + 5 Combine like terms: -8 + 5 = -3 y = -3 Simplifying y = -3
| x+23=-2x+38 | | 0.18x=500-x | | ln(3i)=1.09861229+1.57079633i | | 4x+3(x+2)=90 | | 2x-5/3=13 | | x-2*180=900 | | 2(2x+8)=19 | | 0.18x=450-x | | ln(-6+3i)=1.90333124+2.67794504i | | f(0)=4x-1 | | 0.18x=260-x | | f(11)=11-5 | | x*-x= | | 8x^2-35x-6=0 | | 2x-4=5x+11 | | 5x-2=45x+14 | | (7x+3)+(4x-1)=90 | | 20=8-5(2*-.5-3)+4*-.5 | | -8x-(3x+8)=4-x | | 7x-15=2x-30 | | 12a-a^2=0 | | -9b-b^2=0 | | a(-13+a)=0 | | n(8-n)=0 | | 0.18x=3500-x | | x-7x-60=0 | | f(-4)=4x+5 | | 21^(1/6)/1029^(1/5) | | 2(x+8)=3(x-8) | | 6(x+6)-8=0 | | 49-x^2/21x^3 | | 7-x/3x^5 |